PENGGUNAAN MEDIA PEMBELAJARAN LUDO DALAM MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN BELAJAR SISWA KELAS 4 PADA MATA PELAJARAN BAHASA ARAB DI MIS AL-IKHLASH CIAWILOR KUNINGAN TAHUN AJARAN 2024-2025 - Alfy Mamduh Nuruddin; Gigih Nurhidayat Romis (CV. Lafadz Jaya, 2026)
This classroom action research was motivated by the low learning outcomes of fourth-grade students at MIS Al-Ikhlash, as indicated by interview data with the homeroom teacher showing that 8 out of 18 students (44.4%) scored below the minimum mastery criterion (KKM) of 70 in Arabic language subjects. This issue was attributed to limited instructional innovation and low student engagement during the learning process, leading to student boredom and suboptimal achievement of learning objectives. Therefore, this study aimed (1) to enhance students’ learning engagement in Arabic through the use of Ludo as an instructional media, and (2) to improve students’ learning outcomes using the same approach. This study employed a Classroom Action Research (CAR) design, specifically a collaborative action research model, in which the researcher acted as the instructor assisted by an observer. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected using descriptive analysis techniques, including observation sheets, test results, and documentation of students’ learning outcomes. The findings revealed that the implementation of Ludo as an instructional media significantly improved both student engagement and learning outcomes. Student engagement increased from 45.83% in the first cycle to 87.80% in the second cycle, reflecting an improvement of 41.97%. Similarly, learning outcomes improved, as evidenced by the increase in the number of students achieving mastery: from 5 out of 18 students (27.78%) in the first cycle to 15 students (83%) in the second cycle, indicating a 56% improvement. Based on these findings, it is recommended that teachers adopt more innovative instructional strategies and prepare comprehensive teaching materials, while future researchers are encouraged to further develop Ludo-based learning media by incorporating different variables, indicators, or subject areas.